Government support for SMEs in response to COVID-19: Theoretical model using Wang transform - WANG, Shaun Shuxun (Institutional Knowledge at Singapore Management University, 2021)
Purpose: Many governments are taking measures in support of small and medium-sized enterprises (SMEs) to mitigate the economic impact of the COVID-19 outbreak. This paper presents a theoretical model for evaluating various government measures, including insurance for bank loans, interest rate subsidy, bridge loans and relief of tax burdens. Design/methodology/approach: This paper distinguishes a firm's intrinsic value and book value, where a firm can lose its intrinsic value when it encounters cash-flow crunch. Wang transform is applied to (1) calculating the appropriate level of interest rate subsidy payable to incentivize banks to issue more loans to SMEs and to extend the loan maturity of current debt to the SMEs, (2) describing the frailty distribution for SMEs and (3) defining banks' underwriting capability and overlap index in risk selection. Findings: Government support for SMEs can be in the form of an appropriate level of interest rate subsidy payable to incentivize banks to issue more loans to SMEs and to extend the loan maturity of current debt to the SMEs. Research limitations/implications: More available data on bank loans would have helped strengthen the empirical studies. Practical implications: This paper makes policy recommendations of establishing policy-oriented banks or investment funds dedicated to supporting SMEs, developing risk indices for SMEs to facilitate refined risk underwriting, providing SMEs with long-term tax relief and early-stage equity-type investments. Social implications: The model highlights the importance of providing bridge loans to SMEs during the COVID-19 disruption to prevent massive business closures. Originality/value: This paper provides an analytical framework using Wang transform for analyzing the most effective form of government support for SMEs.